PROSPECTIVE EVALUATION OF HISTOPATHOLOGICAL OUTCOMES FOLLOWING HYSTERECTOMY IN A TERTIARY CARE HOSPITAL (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hysterectomy is one of the most commonly performed gynecological surgical procedures worldwide and is frequently undertaken for various benign uterine conditions. Histopathological examination of hysterectomy specimens is essential for confirming the clinical diagnosis, identifying associated lesions, and evaluating the appropriateness of surgical intervention. This study was conducted to evaluate the histopathological outcomes of hysterectomy specimens and correlate them with the preoperative clinical diagnosis. Methodology: A prospective observational study was conducted in the Department of Pathology in collaboration with the Department of Obstetrics and Gynaecology at Sree Mookambika Institute of Medical Sciences, Kulasekharam, from May 2025 to December 2026. A total of 150 patients who underwent elective abdominal or vaginal hysterectomy for benign gynecological conditions were included. Detailed clinical history, examination findings, imaging studies, and preoperative diagnoses were recorded. All hysterectomy specimens were subjected to detailed histopathological examination, and the findings were correlated with the clinical indications. Statistical analysis was performed using SPSS version 26.0. Results: The majority of patients belonged to the 41–50 years age group (42%). Menorrhagia was the most common presenting complaint (70.6%). Leiomyoma of the uterus was the most frequent clinical indication for hysterectomy (52%), followed by dysfunctional uterine bleeding (30%). Histopathological examination confirmed leiomyoma as the most common lesion, either alone or in association with adenomyosis, chronic cervicitis, cervical intraepithelial neoplasia, and endometrial hyperplasia. Adenomyosis was the predominant histopathological finding among cases clinically diagnosed as dysfunctional uterine bleeding. Conclusion: Leiomyoma and adenomyosis were the most common histopathological lesions in hysterectomy specimens. Histopathological examination remains the gold standard for confirming clinical diagnoses and detecting associated or incidental lesions. Routine evaluation of all hysterectomy specimens is essential for accurate diagnosis and optimal patient management.